2019
DOI: 10.24856/mem.v34i2.962
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Factors and Employee Performance: The Mediating Effect of Employee Empowerment

Abstract: <p>This study analyzes the influence of age, gender, education, years of service, and number of family dependents on employee empowerment both directly and indirectly through employee performance. The sample was taken from 14 cigar companies in Jember Regency, East java, Indonesia, of which each company is represented by ten samples (respondents) who are randomly selected. The samples consist of 140 people. The study uses path analysis to determine the direct and indirect effects of the variables. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 43 publications
3
11
0
Order By: Relevance
“…However, H1 (sex), H4 (department), and H5 (tenure), which also reads "demographic factors sex, department, and tenure influence employees' performance," were not supported, and changes in this variable will not affect employees' performance. The finding of this study concurs with (Hendrawijaya, 2019;Met & Ali, 2014;Oyeniran & Akphorhonor, 2019;Oyewole & Popoola, 2015;Emad and Mohammad, 2016;Omori & Bassey, 2019;Azril, Shaffril & Uli, 2010;Ugwu & Ugwu, 2017) that age, education, has a significant relationship with employees' performance. The findings also agree with Met and Ali (2014) that sex did not affect employees' performance.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…However, H1 (sex), H4 (department), and H5 (tenure), which also reads "demographic factors sex, department, and tenure influence employees' performance," were not supported, and changes in this variable will not affect employees' performance. The finding of this study concurs with (Hendrawijaya, 2019;Met & Ali, 2014;Oyeniran & Akphorhonor, 2019;Oyewole & Popoola, 2015;Emad and Mohammad, 2016;Omori & Bassey, 2019;Azril, Shaffril & Uli, 2010;Ugwu & Ugwu, 2017) that age, education, has a significant relationship with employees' performance. The findings also agree with Met and Ali (2014) that sex did not affect employees' performance.…”
Section: Discussionsupporting
confidence: 88%
“…As illustrated in the framework, it is predicted that independent variables (demographic parameters) such as sex, age, education, department, and tenure influence the dependent variable employees' performance as composite and its dimensions' absenteeism and output. Hendrawijaya (2019) investigated the relationship between demographic factors and employee performance: the role of employee empowerment as a moderator. The stratified sampling method, as well as questionnaires, interviews, and path analysis, were used to sample 140 respondents.…”
Section: Dependent Variablementioning
confidence: 99%
See 1 more Smart Citation
“…Some international non-nursing studies have similarities and differences with the current study. Management research purported that age, gender, education, tenure and dependent family members influence employee empowerment and employee performance (Hendrawijaya, 2019). Likewise, business research found that age and work experience were correlated with psychological empowerment (Dimitriades & Kufidu, 2004).…”
Section: Relationships Of Demographics Qualities and Performances Of Empowered Nursesmentioning
confidence: 99%
“…Moreover, Hendrawijaya (2019), conducted a study about demographic characteristics impact on organizational culture and employee motivation. The study showed that gender and educational levels did not have significant difference among study sample.…”
Section: Discussionmentioning
confidence: 99%